Skillful swimming in age-groups is determined by anthropometrics, biomechanics and energetics - Barbosa, Tiago M. (2019)
This work was supported by the national funding through the Portuguese Foundation for Science and Technology, I.P., under the project UID/DTP/04045/2019, and European Regional Development Fund (FEDER) under the COMPETE 2020 Programme for Competitiveness and Internationalization (POCI) (POCI-01-0145-FEDER-006969). RB is an FCT-Ph.D. scholar (SFRH/BD/142009/2018).